Evaluation of Antioxidant Properties of Residual Hemp Leaves Following Optimized Pressurized Liquid Extraction - Vassilis Athanasiadis; Martha Mantiniotou; Dimitrios Kalompatsios; Ioannis Makrygiannis; Aggeliki Alibade; Stavros I. Lalas (AgriEngineering)
Cannabis sativa, often called hemp, is a medicinal plant belonging to the Cannabaceae family and is widely recognized for its therapeutic applications. After the industrial supercritical CO2 extraction method, hemp residue biomass was recovered, and a significant quantity of bioactive compounds was identified. Therefore, it is of paramount importance to study whether they can be further exploited using green techniques. In the present work, hemp leaf residues were treated using two extraction techniques: one conventional stirring extraction (STE) and one green pressurized liquid extraction (PLE). The latter technique is a promising and swift method for the efficient extraction of valuable molecules from natural sources. The two techniques were optimized through Response Surface Methodology, and the optimized parameters were the appropriate solvent, temperature, and extraction duration. The aim was to maximize the yield of bioactive compounds (polyphenols, flavonoids, and ascorbic acid) from hemp leaf residue and evaluate their antioxidant activity using the most appropriate technique. The results showed that after three 5 min PLE cycles, the recovered individual polyphenols were comparable (p > 0.05) to a 45 min STE (19.34 and 20.84 mg/g, respectively), as well as in antioxidant capacity assays and other bioactive compounds. These findings emphasize the efficacy of the rapid PLE approach as an effective extraction technique to enhance the value of hemp leaf residues while maximizing the concentration of high-added value molecules.